THE USE OF TOMATIS METHOD TO IMPROVE STUDENTSâ LISTENING SKILL - Syam, Ummi Khaerati (Lembaga Perpustakaan Unismuh Makassar, 2012)
This research aimed to know the effectiveness of using Tomatis Method to improve the studentsâ listening skill and to know the student activeness toward teaching learning process through Tomatis Method at the tenth grade students of SMK Negeri 2 Makssar. The method of this research consisted of two cycles. One cycle consisted of four meetings. It means that there were eight meetings for two cycles. As subject in this research was class X in 2012-2013 academic year with studentsâ number as about 36 students, 23 of the students are men and 13 students are women. The instruments of this research were observation sheet and listening test or evaluation. The findings of the research were studentsâ improvement in listening was 64.55 in cycle I and then it became 73.93 in cycle II. The studentsâ participation in learning listening process in the first meeting of cycle I was 59.02% then it became 81.25% in fourth meeting of cycle II.Keywords: Tomatis Method, Listening, Improve.Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan metode Tomatis untuk meningkatkan keterampilan mendengarkan siswa dan untuk mengetahui keaktifan siswa terhadap proses belajar mengajar melalui Metode Tomatis pada siswa kelas X SMK Negeri 2 Makassar. Metode penelitian ini terdiri dari dua siklus. Satu siklus terdiri dari empat pertemuan. Ini berarti bahwa ada delapan pertemuan selama dua siklus. Sebagai subyek dalam penelitian ini adalah kelas X pada tahun akademik 2012-2013 dengan jumlah siswa sebagai sekitar 36 siswa, 23 siswa laki-laki dan 13 siswa perempuan. Instrumen penelitian ini adalah lembar observasi dan tes atau evaluasi mendengarkan. Temuan penelitian ini adalah peningkatan siswa dalam mendengarkan adalah 64,55 pada siklus I dan kemudian menjadi 73,93 pada siklus II. Partisipasi siswa dalam proses belajar mendengarkan di pertemuan pertama siklus I adalah 59, 02% maka menjadi 81, 25% di pertemuan keempat siklus II.Kata Kunci: Metode Tomatis, Mendengarkan, Meningkatkan.